Maternal Nutritional Status and Hemoglobin Level as Predictors of Low Birth Weight - Ni Putu Nita Pebriyani; Made Widhi Gunapria Darmapatni; Ni Luh Putu Sri Erawati; Komang Dedi Juliawan (Jurnal Ilmiah Kebidanan (The Journal Of Midwifery), 2026)
Low birth weight in infants has a risk of stunting 3 times greater than normal birth weight. The incidence of low birth weight in infants is caused by insufficient nutritional intake received by the fetus. Nutritional status during pregnancy can be seen by examining the mid-upper arm circumference (MUAC), hemoglobin levels, and pre-pregnancy BMI. In 2024, there were 3.6% of babies born with low birth weight at Sukasada 1 Community Health Center. This study aims to determine the relationship between MUAC, Hb levels, and BMI during pregnancy with low birth weight at Sukasada 1 Community Health Center. This study used a cross-sectional design conducted from July to October 2025. The study population was 500 respondents using a correlative sample size formula which resulted in a study sample of 104 respondents. This study used secondary data through the Sukasada 1 Community Health Center register with Fisher's Exact Test. The results showed that the incidence of low birth weight at Sukasada 1 Community Health Center for the period January-July 2025 was 8.7%. This study concluded that there was no significant relationship between mid-upper arm circumference, hemoglobin levels, and BMI with the incidence of low birth weight (LBW).